Wrist arthroscopy techniques - Mathoulin, Ch. (Christophe) (Thieme, 2015)
Authored by a renowned expert in the field of hand and wrist surgery, Wrist Arthroscopy Techniques is a step-by-step, anatomically illustrated manual encompassing the latest concepts in the field